Triad of Risk for Late Onset Alzheimer’s: Mitochondrial Haplotype, APOE Genotype and Chromosomal Sex - Wang, Yiwei; Brinton, Roberta D. (Frontiers in Aging Neuroscience, 2016)
The brain is the most energetically demanding organ of the body, and is thus vulnerable to even modest decline in ATP generation. Multiple neurodegenerative diseases are associated with decline in mitochondrial function e.g. Alzheimer’s, Parkinson’s, multiple sclerosis and multiple neuropathies. Genetic variances in the mitochondrial genome can modify bioenergetic and respiratory phenotypes, at both the cellular and system biology levels. Mitochondrial haplotype can be a key driver of mitochondrial efficiency. Herein, we focus on the association between mitochondrial haplotype and risk of late onset Alzheimer’s disease (LOAD). Evidence for the association of mitochondrial genetic variances/haplotypes and the risk of developing late onset Alzheimer’s disease are explored and discussed. Further, we provide a conceptual framework that suggests an interaction between mitochondrial haplotypes and two demonstrated risk factors for Alzheimer’s disease, apolipoprotein E genotype and chromosomal sex. We posit herein that mitochondrial haplotype, and hence respiratory capacity, plays a key role in determining risk of late onset Alzheimer’s and other age-associated neurodegenerative diseases. Further, therapeutic design and targeting that involve mitochondrial haplotype would advance precision medicine for Alzheimer’s disease and other age related neurodegenerative diseases.